A compulsory pop-up form reduces the number of vitamin D requests from general practitioners by 25 percent - Jens K. Munk; Lise Bathum; Henrik L. Jørgensen; Bent S. Lind (Taylor & Francis Group, 2020)
Objective Healthcare costs, including costs for laboratory tests, are increasing worldwide. One example is the measurement of vitamin D. General practitioners in the Capital Region of Denmark include a vitamin D status in approximately 20% of all laboratory requisitions. This study intended to examine the effect of a compulsory pop-up form in the electronic request system on the number of vitamin D tests and to monitor the indications. Design From 1 January 2017, we introduced a compulsory pop-up form in which the general practitioners had to state the indication for measuring vitamin D, choosing from a predefined set of indications. Intervention practitioners were compared with control practitioners before and after the intervention. Setting General practices in the Capital Region of Denmark. Subjects In total, 572 general practitioners and 383,964 patients were included in the period from 1 January 2016 to 31 December 2018. Main outcome measures Number of vitamin D tests and distribution of indications. Results We observed a drop in number of vitamin D requisitions to 70% (in 2017) and 75% (in 2018) relative to 2016. During the same period, the number of requisitions increased by 33% in a non-intervention group of practitioners. The indication 'Monitoring of treatment with vitamin D' was the most frequently used indication, recorded in 121,475 patients. Conclusion A compulsory pop-up form reduces the number of vitamin D requests from general practitioners by 25%. The implication is that pop-up forms can be used to decrease healthcare costs.